Detection of low energy antimatter with emulsions. (30th June 2016) - Aghion, S.; Ariga, A.; Ariga, T.; Bollani, M.; Cas, E. Dei; Ereditato, A.; Evans, C.; Ferragut, R.; Giammarchi, M.; Pistillo, C.; Romé, M.; Sala, S.; et al.
Abstract: Emulsion detectors feature a very high position resolution and consequently represent an ideal device when particle detection is required at the micrometric scale. This is the case of quantum interferometry studies with antimatter, where micrometric fringes have to be measured. In this framework, we designed and realized a new emulsion based detector characterized by a gel enriched in terms of silver bromide crystal contents poured on a glass plate. We tested the sensitivity of such a detector to low energy positrons in the range 10–20 keV . The obtained results prove that nuclear emulsions are highly efficient at detecting positrons at these energies. This achievement paves the way to perform matter-wave interferometry with positrons using this technology.